Camellia sinensis L. Alleviates Pulmonary Inflammation Induced by Porcine Pancreas Elastase and Cigarette Smoke Extract - Dong-Uk Shin; Ji-Eun Eom; Hyeon-Ji Song; Sun Young Jung; Thi Van Nguyen; Kyung Min Lim; Ok Hee Chai; Hyun-Jin Kim; Gun-Dong Kim; Hee Soon Shin; So-Young Lee (MDPI AG, 2022)
Cigarette smoke (CS) is the major factor in the development of chronic obstructive pulmonary disease (COPD), the third leading cause of death worldwide. Furthermore, although Camellia sinensis (CN) has been known as an anti-inflammatory material, the effect of CN has not yet been known on pulmonary inflammation in COPD. Thus, we investigated the protective effects of Camellia sinensis L. extract (CLE) against pulmonary inflammation in porcine pancreas elastase (PPE) and a cigarette smoke extract (CSE)-induced COPD mouse model. Oral administration of CLE suppressed the symptoms such as infiltration of immune cells, cytokines/chemokines secretion, mucus hypersecretion, and injuries of the lung parenchyma. Increased inflammatory responses in COPD are mediated by various immune cells such as airway epithelial cells, neutrophils, and alveolar macrophages. Thus, we investigated the effect and mechanisms of CLE in H292, HL-60, and MH-S cells. The CLE inhibited the expression of IL-6, IL-8, MUC5AC and MUC5B on CSE/LPS-stimulated H292 cells and also suppressed the formation of neutrophil extracellular traps and secretion of neutrophil elastase by inhibiting reactive oxygen species in PMA-induced HL-60 cells. In particular, the CLE suppressed the release of cytokines and chemokines caused by activating the nuclear factor kappa-light-chain-enhancer of activated B via the activation of nuclear factor erythroid-2-related factor 2 and the heme oxygenase-1 pathway in CSE/LPS-stimulated MH-S cells. Therefore, we suggest that the CLE administration be the effective approach for treating or preventing chronic pulmonary diseases such as COPD induced by CS.